The Concepts of Process and Reality in Alfred North Whitehead’s Philosophical Realism and Their Implications in Henrikas Čerapas’s Work (Relevant Tomorrow / Aktualu rytoj, 2024)
The author of the article examines the points of contact between philosophy and painting by exploring whether and how it is possible to convert abstract painting and/or its method into philosophical concepts that explain reality. The work of painter Henrikas Čerapas serves as a case for this exploration. Čerapas’s painting and/or its method is analyzed based on Alfred North Whitehead’s process philosophy. The study has showed that Čerapas’s painting method is based on a materialistic concept of representing reality, i.e., emphasizing the process, action, and materiality of painting; however, at the same time, it is characterized by pronounced idealism. Since these conceptual features are also characteristic of Whitehead’s philosophical realism, Čerapas’s painting method is conceptually close to the fundamental postulates of process philosophy developed by the philosopher.
Keywords: abstract painting; formless painting; painting method; neo-avant-garde; philosophical realism; Henrikas Čerapas’s painting; Gottfried Wilhelm Leibniz’s monadology; Alfred North Whitehead’s process philosophy